Transformational Leadership and Work-Life Balance on Employee Performance through Job Satisfaction - Usdianto Usdianto; Muhammad Amsal Sahban; Rusdiaman Rauf (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the influence of transformational leadership and work-life balance on employee performance, with job satisfaction as a mediating variable, at The Rinra Hotel Makassar. Research Method: This research used a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS 4) method. The population consisted of all 100 employees of The Rinra Hotel Makassar, and a census sampling technique was applied. Data were collected through questionnaires and analyzed to examine direct and indirect relationships among variables. Results and Discussion: The results show that transformational leadership has a positive and significant effect on job satisfaction but does not significantly affect employee performance. Work-life balance has a positive and significant effect on both job satisfaction and employee performance. Job satisfaction does not have a significant direct effect on employee performance and does not mediate the relationship between transformational leadership and work-life balance on employee performance. These findings indicate that transformational leadership is unable to improve employee performance, either directly or through job satisfaction, whereas work-life balance plays a more dominant role in enhancing performance. Implications: This study contributes to human resource management theory and practice in the hospitality industry by emphasizing the importance of work-life balance policies. Organizations are encouraged to strengthen supportive work-life balance practices alongside leadership development to improve employee performance.